1997
DOI: 10.1128/aem.63.3.931-937.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Availability and the Presence of Glyceria maxima on the Composition and Activity of the Dissimilatory Nitrate-Reducing Bacterial Community

Abstract: The effects of nitrate availability and the presence of Glyceria maxima on the composition and activity of the dissimilatory nitrate-reducing bacterial community were studied in the laboratory. Four different concentrations of NO 3 ؊ , 0, 533, 1434, and 2,905 g of NO 3 ؊-N g of dry sediment ؊1 , were added to pots containing freshwater sediment, and the pots were then incubated for a period of 69 days. Upon harvest, NH 4 ؉ was not detectable in sediment that received 0 or 533 g of NO 3 ؊-N g of dry sediment ؊1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Nitrogen‐dissimilating bacteria which are only able to reduce nitrate (NO 2 − accumulators) are known to be well represented in soil and rhizosphere [19,20]. For example, Nijburg et al [21] reported that NO 2 − accumulators accounted for about 40% of the dissimilatory nitrate‐reducing community in the rhizosphere of Glyceria maxima at low NO 3 − concentration. Clays‐Josserand et al [8] showed that NO 2 − accumulators represented 38% of Pseudomonas isolates belonging the fluorescent group in the flax rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen‐dissimilating bacteria which are only able to reduce nitrate (NO 2 − accumulators) are known to be well represented in soil and rhizosphere [19,20]. For example, Nijburg et al [21] reported that NO 2 − accumulators accounted for about 40% of the dissimilatory nitrate‐reducing community in the rhizosphere of Glyceria maxima at low NO 3 − concentration. Clays‐Josserand et al [8] showed that NO 2 − accumulators represented 38% of Pseudomonas isolates belonging the fluorescent group in the flax rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen-dissimilating bacteria which are only able to reduce nitrate (NO 3 2 accumulators) are known to be well represented in soil and rhizosphere [19,20]. For example, Nijburg et al [21] reported that NO 3 2 accumulators accounted for about 40% of the dissimilatory nitrate-reducing community in the rhizosphere of Glyceria maxima at low NO 3 3 concentration. Clays-Josserand et al [8] showed that NO 3 2 accumulators represented 38% of Pseudomonas isolates belonging the £uorescent group in the £ax rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…This species is a common soil heterotroph capable of denitri¢cation isolated from agricultural soils [21] and was the dominant bacterial species isolated from dune soils (De-Boer, personal communication). P. chlororaphis also occurs in the root zone of G. maxima, where it tends to become dominant after amendment with nitrate [22]. We used a strain only capable of reducing nitrate to nitrous oxide [21] for methodological convenience.…”
Section: Bacteriamentioning
confidence: 99%